STRUCTURE AND CHEMICAL COMPOSITION OF THE MAIN ROCK MINERALS OF THE MUCHARIVSKIY GRANITE AREA IN THE NOTH-WESTERN PART OF THE UKRAINIAN SHIELD - BUBNOVA, O.; ANDREIEV, O.; PAVLOV, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The variation of chemical composition of feldspars’ megacrystals and biotite from Mukhariv granite (north-western part of the Ukrainian shield) has been analyzed. Multistage nature of post-magmatic processes has been recognized during mineral transformations of rockforming minerals, which took place in a wide temperature range from amphibolite facies to epidote-amphibolite ones.